2021
DOI: 10.3389/fendo.2021.665521
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Human and Zebrafish Pregnane X Receptor Activities of Pesticides and Steroids Using In Vitro Reporter Gene Assays

Abstract: The nuclear receptor pregnane X receptor (PXR) is a ligand-dependent transcription factor that regulates genes involved in xenobiotic metabolism in mammals. Many studies suggest that PXR may play a similar role in fish. The interaction of human PXR (hPXR) with a variety of structurally diverse endogenous and exogenous chemicals is well described. In contrast, little is known about the zebrafish PXR (zfPXR). In order to compare the effects of these chemicals on the PXR of these two species, we established repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 31 publications
(65 reference statements)
0
4
0
Order By: Relevance
“…The tentative identification of PCL oligomers in the methanolic extracts supports this idea. Because ligands for human and zebrafish PXR are not wholly identical, the activation of zebrafish PXR by PCL and its degradation products will require further investigation. Nonetheless, PXR activity in rats and zebrafish has been reported upon nanoparticle exposure. Whether PXR activation is part of the mechanism of toxicity from exposure to PCL pellets is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The tentative identification of PCL oligomers in the methanolic extracts supports this idea. Because ligands for human and zebrafish PXR are not wholly identical, the activation of zebrafish PXR by PCL and its degradation products will require further investigation. Nonetheless, PXR activity in rats and zebrafish has been reported upon nanoparticle exposure. Whether PXR activation is part of the mechanism of toxicity from exposure to PCL pellets is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The tentative identification of PCL oligomers in the methanolic extracts supports this idea. Because ligands for human and zebrafish PXR are not wholly identical, 95 the activation of zebrafish PXR by PCL and its degradation products will require further investigation.…”
Section: Nanoplastics and Oligomersmentioning
confidence: 99%
“…Previous studies have reported that chemicals have different binding potencies to human and fish receptors. For example, steroids are generally stronger activators of the zebrafish pregnane X receptor, while pesticides are more potent on the human pregnane X receptor . Progestins activate the human progesterone receptor, whereas they act as zebrafish progesterone receptor antagonists .…”
Section: Introductionmentioning
confidence: 99%